Horror vacui : una colección de pintura barroca : catálogo de exposición : Ago 17-Sep 22 de 2017 - Matiz López, Paula Jimena; Villalobos Acosta, María Constanza; Hernández Roa, Juan Francisco; Universidad de Bogotá "Jorge Tadeo Lozano." Museo de Artes Visuales (Editorial Utadeo, 2017)
A collection of baroque paintings made for religious spaces such as the Monastery of Saint Ines of Montepulciano. Among these, a colonial painting "Eterno lo que atormenta, momentáneo lo que deleita" (Eternal what torments, momentary what delights), used in the meditation about death in the novitiate of this same monastery. There are also unpublished works within the category of portraits of dead nuns like the painting La exhumación de sor María Gertrudis Teresa de Santa Inés and the inclusion of several works in the life of Santa Inés, among them, the overdoor (or "supraporte") 18th century series Visión del infierno. Works from the secular world include different Marian, saints and eschatological themes. The catalogue comprises all the works present in the exhibition, all exhibited for the first time to the public.